Frühchristliche Gräber und soziale Anerkennung - Leppin, Hartmut (Zeitschrift für Theologie und Kirche, 2024)
Ancient graves often attest to the striving for recognition of the status of the buried and their family in this world. The low number of graves identified as Christian and the low religious content of the graves that can be identified as Christian should also be seen against this background: there was no need to emphasize the role of the deceased as a Christian; rather, it was often a matter of seeking recognition among Christians and non-Christians alike. Here, an ambiguous self-presentation could make sense, while in Christian contexts, for example in common burial sites, a more openly Christian self-presentation made more sense. With the help of this approach, which certainly cannot be applied to all Christian inscriptions, several epigraphs from Phrygia, including that of Aberkios (Avircius), are interpreted as documents of a self-representation of Christians in a religiously diverse environment.